2011
DOI: 10.1002/art.30435
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of generalized joint laxity (hypermobility) in fourteen‐year‐old children from the UK: A population‐based evaluation

Abstract: Although diagnostic criteria for generalised ligamentous laxity (hypermobility) in children are widely used, they may have limited validity as robust descriptive epidemiology of this condition is lacking. We used a large population-based birth cohort to describe the point prevalence and pattern of hypermobility in children aged 14 years. We performed a cross-sectional analysis of the Avon Longitudinal Study of Parents and Children (ALSPAC). Hyperrmobility was measured at aged 14 years using the Beighton scorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
170
4
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(201 citation statements)
references
References 30 publications
24
170
4
3
Order By: Relevance
“…In general, the result of this study is in accordance with the previous studies on Western populations [3,8,11,16]. The fact that pupils without joint hypermobility were heavier, taller and older could be interpreted as the confirmation of hypothesis that the phenomenon of hypermobility disappears with age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the result of this study is in accordance with the previous studies on Western populations [3,8,11,16]. The fact that pupils without joint hypermobility were heavier, taller and older could be interpreted as the confirmation of hypothesis that the phenomenon of hypermobility disappears with age.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of GJH was studied in different societies and populations. It ranges from 2% to 71% [3,7,8,11,14,[16][17][18][19]. Age, sex, and ethnic subjection have influenced the prevalence of GJH in different societies [2,3,7,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…The agreement between results obtained using these categories and those obtained using the tertiles was good for both the phalangeal and metacarpal 2D:4D ( ϭ 0.72 and ϭ 0.69, respectively). Analyses using these thresholds yielded similar results as were obtained in our primary model (as presented in the report), but the association between low 2D:4D length ratio and knee injury in men was attenuated (odds ratio 1 …”
supporting
confidence: 77%
“…Two previous studies demonstrated an association between low 2D:4D ratio (as a possible marker for prenatal testosterone) and knee OA (1,2). This observed association could possibly be due to a direct effect of testosterone on the cartilage in the prenatal period (3).…”
mentioning
confidence: 85%
See 1 more Smart Citation